What Has the Black Church to do with Public Life? - Pinn, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2013)
The role in public life of religious organizations such as black churches has been a contested and heated topic, with their advocates calling for them to have a major place in public discourse and their critiques demanding their silence in public if not their total destruction. This book offers a creative and compelling way to think about this dilemma. Unlike some, it does not deny the effort on the part of such organizations to be involved in public discourse and public policy; instead, it argues this interest is insufficient. Drawing attention to the basic elements of organizations such as black churches theology, organizational hierarchy, and so on Pinn argues these churches (and other religious organizations by extension) are not structured in such a way as to allow participation in the public arena in ways that appreciate and nurture the diversity of that arena. Instead, Pinn calls for recognition of their value in the private life of some, but their failure to have usefulness within the public arena.
Keywords: Religion and sociology; Ethnicity; African Americans; Religion; Christianity; Sociology of Religion; Ethnicity Studies; African American Culture; Religious Studies, general; Christianity; Social Aspects of Religion